Implementasi Media Pembelajaran Papan Statistika 3M Pada Materi Ukuran Pemusatan Data Dalam Meningkatkan Pemahaman Siswa Kelas VII B mts Hasyim Asy’ari - Wahyuni, Tri (Maliki Interdisciplinary Journal, 2025)
Mathematics is a basic subject that must be present at every level of education, but mathematics learning often causes a decrease in student interest in student learning in class, this also plays a role in decreasing student learning outcomes in mathematics lessons. Mathematics lessons that seem boring and monotonous make students more lazy to follow the lessons, so there needs to be variation in providing mathematics materials in class. The use of 3M Statistics Board learning media for class VII B MTs students can increase student interest in learning mathematics in class, as well as help students to be more accustomed to facing exams or questions related to data centralization and make it easier for students to continue working on the questions that have been given optimally. Based on the research results, it was found that with the 3M Statistics Board learning media, it was able to improve student learning outcomes, which were initially low, to an increase from 55% to 95%, and students' understanding of the questions given increased.